ANALYSIS OF ESTRADIOL AND PROGESTERONE HORMONE LEVELS AGAINST VARIOUS CELL CULTURE IN TCM- 199 MEDIUMFOR CATTLE IN VITRO - Syaiful; F. L.; PURWATI, E.; SUARDI; AFRIANI, T. (Innovare Journal of Medical Sciences, 2017)
Abstract This research was aimed to obtained data base reproductive hormonal profile of the hormones estradiol and progesterone levels in various cell cultures. Culture cells used are cells fallopian tubes, ampulla, isthmus and follicle cells, whereas the culture period used were 0, 2 and 4 days. Analysis of the hormones estradiol and progesterone levels in various cell culture used ELISA method. Data results obtained are the estradiol hormone levels in various cell cultures and periods of different cultures in TCM-199 medium ie cell treatment Fallopian tubes in culture period 0, 2 and 4 days (9.07; 13.14; 9.00 pg/ml), cell culture period ampulla at 0, 2 and 4 days (9.00; 9.29; 14.39 pg/ml), cell isthmus (9.00; 12.08; 9.00 pg/ml) whereas follicular cells in culture period 0, 2 and 4 days (415.04; 476.67; 376.93 pg/ml). The highest levels of the hormone estradiol on cell cultures, namely follicle cells on the second day culture period (476.67 pg/ml), whereas the lowest in cell cultures, namely follicle cells on the fourth day culture period (376.93 pg/ml). Progesterone levels obtained in the treatment of Fallopian tube cells in culture period 0. 2 and 4 days (24.107; 24.644; 24.474 ng/ml), cell culture period ampulla at 0, 2 and 4 days (24.187; 23.753; 24.254 ng/ml ), cell isthmus (24.071; 24.083; 24.034 ng/ml) whereas follicular cells in culture period 0, 2 and 4 days (26.671; 27.610; 24.034 ng/ml). For progesterone levels in various cell culture and the culture that the treatment period follicle cell culture high on the second day culture period (27.610 ng/ml) and low progesterone levels in cell culture ampulla on the second day culture period (23.753 ng/ml). Keywords: Hormones, Cell Culture and Medium TCM-199